Acute ketone supplementation and exercise performance: A systematic review and meta-analysis of randomized controlled trials - Valenzuela, P. L.; Morales, J. S.; Castillo-Garcia, A.; Lucia, A. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To determine the acute effects of ketone supplementation on exercise performance (primary outcome) and physiological and perceptual responses to exercise (secondary outcomes). Methods: A systematic search was conducted in PubMed, Web of Science, and SPORTDiscus (since inception to July 21, 2019) to find randomized controlled trials assessing the effects of acute ketone supplementation compared with a drink containing no ketones (ie, control intervention). The standardized mean difference (Hedges g) between interventions and 95% confidence interval (CI) were computed using a random-effects model. Results: Thirteen studies met all inclusion criteria. No significant differences were observed between interventions for overall exercise performance (Hedges g=-0.05; 95% CI, -0.30 to 0.20; P=.68). Subanalyses revealed no differences between interventions when analyzing endurance time-trial performance (g=-0.04; 95% CI, -0.35 to 0.28; P=.82) or when assessing the separate effects of supplements containing ketone esters (g=-0.07; 95% CI, -0.38 to 0.24; P=.66) or salts (g=-0.02; 95% CI, -0.45 to 0.41; P=.93). All studies reported increases in plasma ketone concentration after acute ketone supplementation, but no consistent effects were reported on the metabolic (plasma lactate and glucose levels), respiratory (respiratory exchange ratio, oxygen uptake, and ventilatory rate), cardiovascular (heart rate), or perceptual responses to exercise (rating of perceived exertion). Conclusions: The present findings suggest that ketone supplementation exerts no clear influence on exercise performance (from sprints to events lasting up to ~50 min) or metabolic, respiratory, cardiovascular, or perceptual responses to exercise. More research is needed to elucidate if this strategy could provide ergogenic effects on other exercise types (eg, ultraendurance exercise).